IMPLEMENTASI E-TAX COURT DAN PERAN ARTIFICIAL INTELLIGENCE UNTUK OPTIMASI KINERJA HAKIM PENGADILAN PAJAK DI INDONESIA - Suharsono, Agus; Prasetyoningsih, Nanik (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2024)
This study analyzes the implementation of the E-Tax Court and proposes the development of using Artificial Intelligence to optimize the performance of Tax Court Judges in Indonesia to make decisions. This doctrinal research uses a legislative, conceptual, and interpretation approach, the data studied in the form of secondary data including primary and secondary legal sources are collected by observation and literature study, which is analyzed using content analysis to make conclusions and recommendations. The study results show that the Supreme Court has already implemented E-Court, which has been proven to simplify and speed up the judicial process and provide legal certainty for justice seekers. In the past year, the Tax Court has also implemented the E-Tax Court to accelerate the process of resolving tax disputes, which from year to year is very large compared to the number of judges, so the performance targets to decide are also huge. This research proposes the development of an E-Tax Court using Artificial Intelligence because, with the right prompt, it can quickly and accurately summarize the long text of the written opinions of the parties to make a judge's opinion in a decision. However, this study does not recommend the use of Artificial Intelligence to make judgments because it is unethical. This research proposal needs further testing before being integrated into the E-Tax Court.